Sectoral Analysis of the Determinants of Corporate Capital Structure in Malaysia - Peng Chow, Yee (Organizations and Markets in Emerging Economies, 2019)
This study investigates the determinants of corporate capital structure of various sectors in the Bursa Malaysia Main Market with the aim to establish whether the determinants of capital structure can be explained by either the trade-off or the pecking order theory. This study also examines whether there are any differences between the regressions for any two sectors or not. This study applies both the ordinary least squares (OLS) and the seemingly unrelated regression (SUR) estimators to estimate the leverage models, and subsequently determines the efficiency of each estimator. The results indicate that profitability, asset tangibility, growth opportunities, and firm size are important determinants of corporate capital structure. However, the signs of the regression coefficients suggest that the trade-o and pecking order theories are complementary. Moreover, the importance of some of these determinants differs across sectors. In most cases of the regression analyses between two sectors, the SUR estimator is found to be more efficient in explaining the determinants of capital structure among the various sectors. Hence, this study concludes that the SUR method could serve as a useful alternative methodology for capital structure research.